ANALGESIC EFFICACY OF ULTRASOUND GUIDED BILATERAL SUBCOSTAL TRANSVERSUS ABDOMINIS MUSCLE PLANE BLOCK AND PORT SITE INFILTRATION WITH BUPIVACAINE IN LAPAROSCOPIC CHOLECYSTECTOMY - Ali, Muhammad; Syed Hafiz Majid Waseem; Khan, Sidra; Abdullah; Zulfiqar Haider; Iftikhar Ali (Journal of Postgraduate Medical Institute, 2023)
Objective: To evaluate the postoperative analgesic efficacy of ultrasound-guided bilateral subcostal transversus abdominis plane block in comparison to port-site local anesthetic infiltration in patients undergoing elective laparoscopic cholecystectomy. Methodology: It was a Quasi experimental study, conducted in Combined Military Hospital Rawalpindi, over 6 months, from 13/4/21 till 13/10/2021. Patients numbering 92 of both genders fulfilling inclusion criteria were incorporated and placed into 2 groups equally. Group O (n=46) underwent ultrasound guided bilateral subcostal transversus abdominis plane block using 0.25% bupivacaine with volume dosage of 0.4ml/kg divided by 2, one part for each side. In Group-P (n=46) total dose of bupivacaine (0.25%, volume dose of 0.4ml/kg) was divided by total number of ports used and one portion was infiltrated at each port-site at the completion stage of surgery. Post-operative pain score, quantity of post-operative analgesia and patient satisfaction scores were calculated. Results: Mean tramadol usage in Group-O was 109.56 ± 15.04 mg compared with 155.21 ± 22.18 mg of Group-P (p value <0.001 for both). Visual Analog pain scores were lesser in Group-O all the times. Patient satisfaction scores were 3.30 ± 0.66 and 2.71 ± 0.98 for Group-O and Group-P respectively. Conclusion: Ultrasound guided subcostal Transversus abdominis plane block is effective in contributing to post-operative analgesia following laparoscopic cholecystectomy and is superior to port site infiltration. It decreases pain scores, post-operative analgesia requirement and increments patient satisfaction compared with port-site infiltration.